Islamic Financial Literacy on Saving and Investment Decision: The Individual Attitude Effect - Atif, Hussain; Asri, Marsidi; Rossazana, Ab. Rahim (Human Resource Management Academic Research Society (HRMARS), 2024)
This research offers several appealing features for an analysis of Islamic financial Literacy and personal financial management. Individual attitudes intention and behavior are added as the moderating variable on that association. This study explores the relationship between individual attitude intention and behavior and personal financial management from an empirical perspective. Specifically, by conducting a survey in Sarawak, this research analyses the influence of individual attitude intention and behavior on personal financial management at the individual level focusing on the demographic profiles and financial literacy level. Individual attitudes are classified into individual behavior and intention of the respondents toward Islamic financial literacy and management of the personal financing’ openness to experience, Islamic financial knowledge exert relatively large influences on personal financial management in terms of the levels of Islamic financial literacy held by everyone. In contrast, openness to experience and agreeableness appear to be unimportant in influencing personal financial management. The findings also suggest that Individual attitude have different moderating effects with Islamic financial knowledge. while individual is found to have positive moderating effect with Islamic financial knowledge towards personal financial management, where the intention has also moderated effect at all.